Efektivitas Pengamanan Barang Milik Negara (BMN) Berupa Peralatan Kantor di Lembaga Penyiaran Publik Radio Republik Indonesia (LPP RRI) Surakarta - Shephia Candra Prasiskasari; Budi Istiyanto (Pusat Riset dan Inovasi Nasional, 2025)
Securing State Property (BMN) is one of the stages of the state property cycle to protect goods from the risk of loss, damage, and misuse. The purpose of this study is to determine the effectiveness of procedures for securing state property for office equipment at LPP RRI Surakarta. The research method used is descriptive qualitative research. The data collection techniques used by the author include observation, interviews, and review of documents and archives. Based on the author's research results at LPP RRI Surakarta, securing state property for office equipment is said to be effective but not optimal. The security process is carried out in accordance with the Peraturan Menteri PUPR No. 30 of 2020 and is completed on time. Activities are carried out with accurate measurements and are on target and objective. Although there are errors in the installation of barcode labels, the Decree for the Application for Use Status is missing, and users who move goods do not comply with the provisions, so improvements need to be made to increase the effectiveness of securing state property for office equipment at LPP RRI Surakarta.